Rhodiola yushuensis, a new species of Rhodiola (Crassulaceae) from Qinghai, China - Rong, Yu-Lin; Li, Guo-Dong; Zheng, Hai-Lei; Zhang, Jun; Meng, Shi-Yong (Phytotaxa, 2022)
A new species from the Qinghai-Tibetan Plateau is described and illustrated. Rhodiola yushuensis S.Y. Meng et J. Zhang sp. nov. is similar to Rhodiola smithii (Hamet) S. H. Fu, but it differs in its inner caudex leaves with obvious petioles and the leaf blades are obovate-triangular (vs. inner caudex leaves with strongly descends to the base of the petiole, and the leaves are long linear) and the outer caudex leaves are scalelike, triangular-suborbicular (vs. scalelike, narrowly triangular). Principal component analysis (PCA) analysis of the leaf traits and seed coat architecture also showed that R. yushuensis can be separated from R. smithii. The nrDNA internal transcribed spacer (ITS) sequences also support the claim that this plant is a new species, and it is grouped with R. smithii.